1990
DOI: 10.1080/00288306.1990.10425698
|View full text |Cite
|
Sign up to set email alerts
|

Ferromanganese nodules of the Southwestern Pacific: Results of Soviet investigations

Abstract: As shown by several Soviet expeditions on RY Vityaz and Dmitry Mendeleyev the pelagic abyssal basins of the Southwestern Pacific represent a prominent Fe-Mn nodule field, which is associated with the centre of the southern subtropical anticyclonal gyre and is characterised by extremely slow sedimentation rates of eupelagic and zeolitic clay. Nodule abundance is commonly high (up to 70.8 kg,lm 2 ), but variable.The nodules are of hydrogenetic type with low Mo, Ni, and Cu content and Mn/Fe ratio. However, the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that the sediments in this region are dominantly pelagic clays, with sedimentation rates <1 mm/10 3 yr (Piper et al, 1985(Piper et al, , 1987, and that almost the whole area south of 36ºS is covered by manganese nodules with surface densities of up to 75%-100%, with some massive manganese crusts observed locally (Glasby, 1976b;Plüger et al, 1985;Plüger, 1989, personal commun. ;Skornyakova et al, 1990). Berger et al (1976) have estimated the Carbonate Compensation Depth (CCD) in this region to be ~4,200 m.…”
mentioning
confidence: 99%
“…Previous studies have shown that the sediments in this region are dominantly pelagic clays, with sedimentation rates <1 mm/10 3 yr (Piper et al, 1985(Piper et al, , 1987, and that almost the whole area south of 36ºS is covered by manganese nodules with surface densities of up to 75%-100%, with some massive manganese crusts observed locally (Glasby, 1976b;Plüger et al, 1985;Plüger, 1989, personal commun. ;Skornyakova et al, 1990). Berger et al (1976) have estimated the Carbonate Compensation Depth (CCD) in this region to be ~4,200 m.…”
mentioning
confidence: 99%